2010
DOI: 10.1021/la100174h
|View full text |Cite
|
Sign up to set email alerts
|

Application of Poly(amidoamine) Dendrimers for Use in Bionanomotor Systems

Abstract: The study and utilization of bionanomotors represents a rapid and progressing field of nanobiotechnology. Here, we demonstrate that poly(amidoamine) (PAMAM) dendrimers are capable of supporting heavy meromyosin dependent actin motility of similar quality to that observed using nitrocellulose, and that microcontact printing of PAMAM dendrimers can be exploited to produce tracks of active myosin motors leading to the restricted motion of actin filaments across a patterned surface. These data suggest that the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The relationship between velocity and contact angle was however, different in a study (Kolli et al 2010) comparing motility on nitrocellulose (contact angle ~87°), microcontact printed poly(amidoamine) dendrimers (contact angle ~47°) and 3-mercaptopropyl trimethoxysilane (~68°). Here, no motility was found on the silanized surface but similar motility was observed on nitrocellulose and the dendrimer, in spite of widely varying contact angles.…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 94%
See 2 more Smart Citations
“…The relationship between velocity and contact angle was however, different in a study (Kolli et al 2010) comparing motility on nitrocellulose (contact angle ~87°), microcontact printed poly(amidoamine) dendrimers (contact angle ~47°) and 3-mercaptopropyl trimethoxysilane (~68°). Here, no motility was found on the silanized surface but similar motility was observed on nitrocellulose and the dendrimer, in spite of widely varying contact angles.…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 94%
“…Particularly for high contact angles (>70°) the effects on velocity show appreciable variability. Whereas Nicolau et al (2007) found a decrease in velocity for contact angles >70°, Kolli et al (2010) obtained high-quality motility on nitrocellulose with contact angle >80°. In our studies (unpublished) we have observed reduced velocity in occasional experiments with more extensive silanization and a contact angle beyond 80°.…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of nanomotors to power the transport of synthetic components is a current goal of several nanoengineering research areas, as this approach may allow for the controlled transport of single molecules in the absence of bulk flow [2][3][4][5][6]. Indeed, recent studies have reported the use of catalytic-metallic [7][8][9], microtubule-kinesin [10][11][12][13][14] and actin-myosin motor systems [15][16][17][18] for nanotransport applications, while other work has also suggested that these biomachines may also be useful for the development of new types of nano-communication where the information signal is propagated under the power of nanomotors [19].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts towards developing nanomotor-based cargo transport systems have thus far largely centered on controlling the directional movement of the motors themselves or the direction of filament movement through the use of topographical tracks [9,11,16], hydrophobic/hydrophilic surface patterning [17] and chemical modification of the substrate by microcontact printing [18]. To date, most of the work in this area has utilized the microtubulekinesin motor system [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%